Tone Enhancement Electro‐Fiberscope Combined with Strobe Light Source and Re‐analysis Past Images‐Tone Enhancement Dynamic Stroboscope. (18th June 2022) - Tsunoda, Koichi; Nagai, Ryoto; Kobayashi, Rika; Takazawa, Mihiro; Wasano, Koichiro; Kondo, Kenji
Abstract : Tone enhancement electro fiberscope combined with strobe light source is benefit for dynamic observation of vocal fold vibration, mucosal waves and voice, it also may be effective for early detection of cases of glottal cancer rather than ordinate stroboscopic examination or simple NBI observation. Laryngoscope, 132:2206–2208, 2022